PENERAPAN ALGORITMA NORTH WEST CORNER DALAM PENYELESAIAN MASALAH TRANSPORTASI - Chandra, Tintin (STMIK TIME, 2016)
Companies with many branches will be thinking about the best solution in allocating units to the number of requests both within the same or different regions of Goods that are not distributed to the request will cause some of the effects of such supplies become out of date, damaged, and would also result in the cost of rental of warehouses also increased. For the distribution of goods from one place to another, require tools such as transportation. The distribution of goods is not only dependent on the distribution channel but also the unit that will be distributed. Haulage businesses do not want to lose by making the provision of goods to be distributed to the scales will be rounding up, say 0, 4 kg is calculated to be 1 kg. Studies conducted in the method of transportation is the North West Corner method by assuming that the demand and supply are in the same area. Some of the modules used in solving transportation methods that check module, the module is calculated, the random module cost as well as several other modules. The overall result of the application of alogritma North West Corner can be seen in Figure 1. where in the application there is a size. Sizes are filled indicate the size of a square matrix starting from a minimum of 3 and maximum of 6. The Implementation of Algorithms North West Corner in problem solving transportation unit that can map to local demand. Total cost of the transportation of the implementation of the algorithm is multiplied by the capacity between the cost of inventory with a request.